Surgical Window and Treatment Strategy for Patient with Multiple Fractures Escaping Inflammatory Response: A Case Report - Shakya , Sujan; Ming , Liu (Europasian Journal of Medical Sciences, 2021)
Today’s Orthopedic surgeons must be adept at the evaluation and management of complicated Multiple Injured Patients (MIP). Despite dynamic strategies, advance modern medical care, the mortality rate of 50-70% has been reported due to high-velocity accidental cases with femoral shaft fractures associated with pelvic fractures and injuries to other organs. We hereby present an interesting case of MIP with the unstable pelvic acetabulum, ipsilateral femoral shaft fracture, floating elbow, and distal radius fracture. It is essential to follow an optimal protocol for such complex fractures. Therefore, we stated the appropriate surgical window and treatment intervention to fix all the major fractures by overcoming the hyperinflammatory state. DOI: https://doi.org/10.46405/ejms.v3i2.259